QoE utility function-based cross-layer resource allocation in multi-user MIMO-OFDM systems - Da-ming WANG; Song CHEN; Wei-jia CUI; Qiang WANG (Tongxin xuebao)
Resource allocation problem was investigated for downlink multi-user MIMO-OFDM systems.A QoE (quality of experience) utility function was given according to the characteristics of real-time (RT) and non real-time (NRT) ser-vices,and then a RT ＆amp; NRT QoE utility function-based cross-layer resource allocation algorithm was proposed.The al-gorithm firstly used the designed utility function to calculate the delta QoE,which was offered by users got resource.Secondly,it classified users according to their delta QoE and then allocated time-frequency blocks.Thirdly,it optimized the power allocation result by implementing pseudo water flooding power allocation.Simulation results show that com-pared with the existing algorithm,the proposed algorithm is better in the user average QoE,average packet delay to real time services,average packet lost rate to non real time services as well as sum throughput of system.